Juridical Analysis Of Advocacy Switching Reviewed From Advocate Law - Muhammad Ali Sariati (Jurnal Hukum Khaira Ummah, 2021)
This study aims to determine and analyze the mechanism for taking the Advocate's oath after the issuance of the Letter of the Chief Justice of the Supreme Court Number 73/KMA/HK./IX 2015, as well as analyzing the suitability of the Letter of the Chief Justice of the Supreme Court Number 73/KMA/HK.01/IX/2015 in accordance with Article 28 paragraph (1) of Law Number 18 of 2003 concerning Advocates. This type of research is included in the typology of normative legal research, which is a research based on legal materials, both primary and secondary legal materials.Second,The provisions of Article 28 of Law Number 18 of 2003 concerning Advocates emphasize that there is only one organization of Advocates with the aim and purpose of improving the quality of the advocate profession but in fact the purpose of the establishment of Law Number 18 of 2003 concerning Advocates is to limit the Advocate Organization to only one the organization has changed so that there is no longer a limit on the organization of advocates, so that the organization of advocates becomes more and more controlled as a result of the enactment of the Chief Justice of the Supreme Court Number: 073/KMA/HK.01/IX/2015